Studies on wall pressure flow control by micro jets for high area ratio - Ashfaq, Syed; Khan, Sher Afghan (RS Publication, 2014)
This paper discuss the experimental results on the flow characteristics of a suddenly expanded flow from the convergent nozzle for subsonic Mach numbers. An Active control in the form of micro jets were used to investigate the effectiveness of micro jets on wall pressure flow field in the enlarged duct. Accordingly an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The Mach numbers of the present studies were M = 0.9, 0.8, and 0.6 and the area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied was 6.25. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. From the results, it is seen that the flow in the base region is dominated by the waves, however, the magnitude of the waves has reduced considerably due to the very high area ratio, also, it is found that for L/D in the range L/D = 10 and 8 the flow remains oscillatory for all the Mach numbers. However, these oscillations are suppressed gradually either with the decrease in the L/D ratio in the range 3 to 6 or with decrease in the level of inertia level. The minimum suddenly expanded duct length required for the flow to be attached is the present study has shown that the wall pressure in a suddenly expanded axi-symmetric duct can be controlled by employing micro jets at the base. It is found that the flow field in the enlarged duct with and without control remained the same hence, we summarized that active control in the form of micro jets are not disturbing the field.